Comprehensive Survey of the Distribution of Colour and Phenolics of Different Red Grape Wine Vineyard Blocks from the Robertson Area in South Africa - van der Merwe, H.; Nieuwoudt, H.; de Beer, D.; du Toit, W.J. (South African Journal of Enology and Viticulture, 2016)
Colour and phenolic content of red grapes are two of the most important constituents required to produce a quality red wine. In the Robertson grape growing area, difficulty is sometimes experienced with colour development of grapes. This is especially linked to location and most probably greatly influenced by season. Forty four vineyard blocks of the cultivars Pinotage, Merlot, Cabernet Sauvignon and Shiraz, were studied over 3 seasons primarily to focus on colour and phenolic content, but secondly on total soluble solids, titratable acidity and pH of the grapes. High performance liquid chromatography and spectrophotometric methods were used to determine various colour and phenolic parameters present at harvest. This data was used to indicate how colour and phenolic constitution of a part of the Robertson grape growing area was distributed in relation to various factors, such as cultivar and season. GPS points were used to map data for the blocks visually. Results showed variable colour and phenolic content for these grapes based on blocks and phenolic compounds investigated. Shiraz displayed a wider distribution of certain phenolic compounds over the three seasons than the other 3 cultivars. Seasonality had a great influence on these results, with outlying blocks being identified.